2018
DOI: 10.3389/fphar.2018.00517
|View full text |Cite
|
Sign up to set email alerts
|

Coptisine Induces Apoptosis in Human Hepatoma Cells Through Activating 67-kDa Laminin Receptor/cGMP Signaling

Abstract: Hepatocellular carcinoma (HCC) is the most common primary cancer of the liver. Hence, new anti-liver cancer treatment strategies need to be urgently developed. Coptisine is a natural alkaloid extracted from rhizoma coptidis which exhibits anticancer activity in various preclinical models, including liver cancer. However, the molecular mechanisms underlying the anti-liver cancer effects of coptisine remains unclear. We used flow cytometry to assess the binding of coptisine to 67LR expressed on the surface of SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Production of NO causes an increase of cGMP, produced by NO-dependent soluble guanylate cyclase (sGC) activation, and then the phosphorylation of PKCδ [74] (Figure 1). Furthermore, more recently, it has been observed that the anticancer agent coptisine induces apoptosis in hepatocellular carcinoma (HCC) cells via the 67LR/cGMP pathway [163]. Conversely, several studies reported that EGCG negatively regulates eNOS/NO production in different cancer types [75,76,77,78] and also sGC/cGMP amount [96].…”
Section: 67-kda Laminin Receptor Signalling Pathwaysmentioning
confidence: 99%
“…Production of NO causes an increase of cGMP, produced by NO-dependent soluble guanylate cyclase (sGC) activation, and then the phosphorylation of PKCδ [74] (Figure 1). Furthermore, more recently, it has been observed that the anticancer agent coptisine induces apoptosis in hepatocellular carcinoma (HCC) cells via the 67LR/cGMP pathway [163]. Conversely, several studies reported that EGCG negatively regulates eNOS/NO production in different cancer types [75,76,77,78] and also sGC/cGMP amount [96].…”
Section: 67-kda Laminin Receptor Signalling Pathwaysmentioning
confidence: 99%
“…Coptisine is a type of isoquinoline alkaloid extracted from Rhizoma coptidis (roots of Coptis chinensis Franch) [ 12 , 13 ], and its pharmacological properties against inflammation [ 14 ], bacterial infection [ 15 ], and metabolic diseases [ 16 , 17 ] are well established. Recent studies have shown that this compound has an anticancer effect on lung, colorectal, breast, and liver cancers [ 18 , 19 , 20 , 21 , 22 ]. For example, Han et al [ 19 ] demonstrated that coptisine induced apoptotic cell death through reactive oxygen species (ROS) production, a decline of mitochondrial membrane potential (MMP, ΔΨm), and activation of mitochondrial-associated apoptosis in human colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizoma coptidis, which is called as ”Huang Lian” in China, is an important herbal medicine that contains alkaloids, such as berberine, coptisine, palmatine, jatrorrhizine [ 10 ]. As reported, Coptisine exhibited numerous pharmacological activities, such as antibacterial, anti-hyperlipidemic, anticachectic, and antitumor properties [ 11 , 12 ]. Previous studies have demonstrated that coptisine could block activation of mitogen-activated protein kinase (MAPK), PI3K/Akt and nuclear factor kB(NF-kB) pathways in macrophages, and accordingly inhibit LPS-induced inflammatory reaction [ 13 ].…”
Section: Introductionmentioning
confidence: 99%